Influência da hipertensão arterial sistêmica e doença arterial periférica em pacientes com disfunção erétil - Spessoto, Luís Cesar Fava (2012)
Introduction: The assessment of erectile dysfunction (ED) as an early symptom of endothelial dysfunction and atherosclerosis may be important to the identification of patients at high cardiovascular risk. Objective: The aim of the present study was to investigate the influence of systemic arterial hypertension (SAH) and peripheral artery disease (PAD) in patients with ED. Patients and Methods: One hundred twenty-five patients with ED (mean age: 59.82 ± 10.48 years; range 19 to 88), regardless of race, from the region of São José do Rio Preto, state of São Paulo, Brazil were evaluated between March and October 2011. ED was classified as mild (Grade 1), moderate (Grade 2) and severe (Grade 3), based on an international questionnaire. The physical exam was guided by the ankle-brachial index (ABI), with values below 0.9 indicating PAD. Data analysis involved Pearson s chi-squared test, Fisher s exact test and the Kruskal-Wallis test for the comparison of ABI values based on combined SAH-ED, using the Bonferroni correction. Dependence analysis was employed to determine the following associations: ED x ABI, ED x SAH, SAH x ABI and SAH x ABI x ED. Logistic regression analysis was performed to relate the degree of ED with the combination of SAH and ABI, considering a 5% alpha error. Results: Among the 125 patients studied, 22 (17.6%) had mild ED, 50 (40.0%) had moderate ED and 53 (42.4%) had severe ED. Regarding the ABI, 40 (32.0%) patients had values equal to or greater than 0.9, whereas 85 (68.0%) have values lower than 0.9, indicting the occurrence of PAD. The comparison between the median ABI of patients with different degrees of ED demonstrated significant differences between Grades 1 and 3 (p = 0.0009) as well as between Grades 2 and 3 (p = 0.0131). The dependence diagram revealed the following: 1) Grade 3 ED was associated with PAD in the comparison between patients with ABI < 0.9 and those with ABI ≥ 0.9 (p = 0.013); 2) Grade 3 ED was associated with SHT in the comparison between normotensive and hypertensive patients (p = 0.002); 3) Grade 3 ED was associated with SAH + PAD in the comparison between normotensive and hypertensive patients with ABI < 0.9 and normotensive and hypertensive patients with ABI ≥ 0.9 (p = 0.002). In patients with PAD, hypertensive patients exhibited Grade 3 ED more than normotensive patients (p = 0.015). The logistic regression of the association between ED and the SAH-ABI combination with the reference N-ABI ≥ 0.9 demonstrated a tendency (p < 0.0005) toward an increased risk of a greater degree of ED obeying the following order: SAH-ABI ≥ 0.9, SAH-ABI < 0.9 and N-ABI < 0.9. Conclusions: The impairment of the ED grade corresponds to a decrease of ABI, suggesting evolution of PAD in these patients. There was a significant association among Grade 3 ED x PAD, Grade 3 ED x SAH, and SAH x PAD. Hypertensive patients exhibited Grade 3 ED significantly more than normotensive patients. Systemic arterial hypertension may have a compensatory effect against erectile dysfunction in patients with peripheral arterial disease.